Pregled dejavnosti raziskovanja v kontekstu izobraževanja za socialno delo v Sloveniji - Rihter, Liljana (Socialno delo, 2019)
Research in connection with social work education in Slovenia has been in existence for fifty years. During that period, over 170 research and development projects have been carried out that have significantly (co)influenced the development of social work practice and theory and social work education. The guidelines and global standards for social work education give great importance to research. An analysis of the research and development work (themes, purposes, populations, funding) performed since 1969 shows that we (social work educational institution) follow these guidelines. In addition to the basic purpose - to develop the practice and theory of social work - we have also been engaged in broader social and political topics (social protection and social policy) and the social status of populations who use social welfare services. The research findings enabled the development of study contents and the adaptation of social work studies to the current situation in society. In the prevailing period of neo-liberalism, scientific research and reflection on the social context are urgently needed, which is often hindered by the predominant way of financing research activity on the basis of the set topics decided by decision-makers, which does not necessarily coincide with the perceived needs or interests of researchers.
Keywords: Fakulteta za socialno delo; financiranje; socialna politika; socialno delo; socialno varstvo; študijski programi